Revisiting roles of mast cells and neural cells in keloid: exploring their connection to disease activity - Yeo, Eunhye; Shim, Joonho; Oh, Se Jin; Choi, YoungHwan; Noh, Hyungrye; Kim, Heeyeon; Park, Ji-Hye; Lee, Kyeong-Tae; Kim, Seok-Hyung; Lee, Dongyoun; Lee, Jong Hee (Frontiers in Immunology, 2024)
Background Mast cells (MCs) and neural cells (NCs) are important in a keloid microenvironment. They might contribute to fibrosis and pain sensation within the keloid. However, their involvement in pathological excessive scarring has not been adequately explored. Objectives To elucidate roles of MCs and NCs in keloid pathogenesis and their correlation with disease activity. Methods Keloid samples from chest and back regions were analyzed. Single-cell RNA sequencing (scRNA-seq) was conducted for six active keloids (AK) samples, four inactive keloids (IK) samples, and three mature scar (MS) samples from patients with keloids.The scRNA-seq analysis demonstrated notable enrichment of MCs, lymphocytes, and macrophages in AKs, which exhibited continuous growth at the excision site when compared to IK and MS samples (P = 0.042). Expression levels of marker genes associated with activated and degranulated MCs, including FCER1G, BTK, and GATA2, were specifically elevated in keloid lesions. Notably, MCs within AK lesions exhibited elevated expression of genes such as NTRK1, S1PR1, and S1PR2 associated with neuropeptide receptors. Neural progenitor cell and non-myelinating Schwann cell (nmSC) genes were highly expressed in keloids, whereas myelinating Schwann cell (mSC) genes were specific to MS samples. Conclusions scRNA-seq analyses of AK, IK, and MS samples unveiled substantial microenvironmental heterogeneity. Such heterogeneity might be linked to disease activity. These findings suggest the potential contribution of MCs and NCs to keloid pathogenesis. Histopathological and molecular features observed in AK and IK samples provide valuable insights into the mechanisms underlying pain and pruritus in keloid lesions.